Позднеплейстоценовые слепушонки (Rodentia, Ellobius) Украины - Рековец, Л.И. (Вестник зоологии, 1985)
Ellobius talpinus palaeoucrainicus ssp. n. is described from Late Pleistocene alluvial deposits of the Dnieper. From closely related recent forms it differs by larger body size, higher relative indices of the lower jaw diastemal part, less developed tracks. The degree of variation of certain characters during Pleistocene is outlined.